Benzodiazepine Use in Older Adults in the United States, Ontario, and Australia from 2010 to 2016. Issue 6 (12th February 2018) - Brett, Jonathan; Maust, Donovan T.; Bouck, Zach; Ignacio, Rosalinda V.; Mecredy, Graham; Kerr, Eve A.; Bhatia, Sacha; Elshaug, Adam G.; Pearson, Sallie A.
Abstract : OBJECTIVES: To detail annual trends in benzodiazepine incidence and prevalence in older adults between 2010 and 2016 in three countries. Design: Observational multicountry cohort study with harmonized study protocol. Setting: The United States (veteran population); Ontario, Canada; and Australia. Participants: All people aged 65 and older (8, 270, 000 people). Measurements: Annual incidence and prevalence of benzodiazepine use stratified according to age group (65–74, 75–84, ≥85) and sex. We performed multiple regression analyses to assess whether rates of incident and prevalent use changed significantly over time. Results: Over the study period, we observed a significant decrease in incident benzodiazepine use in the United States (2.6% to 1.7%) and Ontario (6.0% to 4.4%) but not Australia (7.0% to 6.7%). We found significant declines in prevalent use in all countries (United States: 9.2% to 7.3%; Ontario: 18.2% to 13.4%; Australia: 20.2% to 16.8%). Although incidence and prevalence increased with age in Ontario and Australia, they decreased with age in the United States. Incidence and prevalence were higher in women in all countries. Conclusion: Consistent with other international studies, there have been small but significant reductions in the incidence and prevalence of benzodiazepine use in older adults in all three countries, with the exception of incidence in Australia, although use remains inappropriately high—particularly in those aged 85 and older—which warrants further attention from clinicians and policy‐makers.